Risk Factors for Severe Postoperative Complications after Oncologic Right Colectomy - Samer Ammar Khel; Mousa Elregieg (AlQalam Journal of Medical and Applied Sciences, 2024)
This study aims to examine the possible risk factors for severe postoperative sequelae following oncologic right colectomy. This retrospective analysis included all consecutive patients with right colon cancer who had right colectomy in our department from 1st Jan 2022 to 31st Dec 2023. The Clavien-Dindo grading system was employed to assess postoperative problems. Univariate and multivariate logistic regression analysis were done to look into risk variables for serious postoperative complications. Of the 21 patients, there were 10 males and 11 females, with a median age of 68 (IQR 60–78). Postoperative morbidity and mortality rates were 42.85% (9 patients) and 9.52% (2 patients), respectively. The anastomotic leak rate was 4.76% (1 patient). Severe postoperative complications (Clavien–Dindo grades III–V) were present in 3 patients (14.28%). Univariate analysis showed the following as risk factors for postoperative severe complications: Charlson score, lack of mechanical bowel preparation, level of preoperative proteins, blood transfusions, and degree of urgency (elective/emergency right colectomy). In the logistic binary regression, the Charlson score (OR = 1.932, 95% CI = 1.077–3.463, p = 0.025) and preoperative protein level (OR = 0.048, 95% CI = 0.006–0.433, p = 0.007) were found to be independent risk factors for postoperative severe complications. Severe consequences after oncologic right colectomy are linked to a low preoperative protein level and a higher Charlson comorbidity index. تهدف هذه الدراسة إلى دراسة عوامل الخطر المحتملة لعقابيل ما بعد الجراحة الشديدة بعد استئصال القولون الأيمن للأورام. شمل هذا التحليل بأثر رجعي جميع المرضى المتتاليين المصابين بسرطان القولون الأيمن والذين خضعوا لعملية استئصال القولون الأيمن في قسمنا من 1 يناير 2022 إلى 31 ديسمبر 2023. تم استخدام نظام تصنيف Clavien-Dindo لتقييم مشاكل ما بعد الجراحة. تم إجراء تحليل الانحدار اللوجستي أحادي المتغير ومتعدد المتغيرات للنظر في متغيرات الخطر لمضاعفات ما بعد الجراحة الخطيرة. كان هناك 17 مريضا، 8 ذكور و 9 إناث، بمتوسط عمر 68 (معدل الذكاء 59-75). وكانت معدلات المراضة والوفيات بعد العملية الجراحية 35.29٪ (6 مرضى) و 11.76٪ (مريضان)، على التوالي. وكان معدل التسرب المفاغرة 5.88٪ (مريض واحد). حدثت مشاكل حادة بعد العملية الجراحية (الدرجات Clavien-Dindo من الثالث إلى الخامس) في مريضين (11.76٪). كشف التحليل أحادي المتغير عن متغيرات الخطر التالية للمضاعفات الشديدة بعد العملية الجراحية: درجة تشارلسون، عدد البروتينات قبل الجراحة، عمليات نقل الدم. في الانحدار الثنائي اللوجستي، تم الكشف عن درجة تشارلسون (OR = 1.931، 95٪ CI = 1.077-3.463، p = 0.025) ومستوى البروتين قبل الجراحة (OR = 0.049، 95٪ CI = 0.006-0.433، p = 0.007) عوامل الخطر المستقلة للعقابيل الشديدة بعد العملية الجراحية. ترتبط العواقب الوخيمة بعد استئصال القولون الأيمن للورم بانخفاض مستوى البروتين قبل الجراحة وارتفاع مؤشر الاعتلال المشترك لتشارلسون.